Exploring key factors associated with training quality among elite para-athletes. A qualitative study - Øvstehage, Vemund; Sandbakk, Silvana Bucher; Kocbach, Jan; Sandbakk, Øyvind (Frontiers in Sports and Active Living, 2025)
IntroductionDespite extensive research on training load characteristics, knowledge about training quality remains sparse. Training quality encompasses two dimensions: quality in the training process and quality in specific training sessions. Elite para-athletes perform high volumes of training, and their training execution may be further influenced by their impairment and sport. No research has explored training quality among elite para-athletes. Therefore, the aim of this study was to qualitatively explore key factors associated with training quality among elite para-athletes across different impairments and sports.MethodsA hermeneutic phenomenological approach was applied to conduct semi-structured interviews with 21 Norwegian current and former elite para-athletes (10 women and 11 men) from ten sports and five impairment categories. A reflexive thematic analysis was conducted to inductively explore the experiences and perspectives related to training quality in the training process and specific training sessions. Methodological integrity was ensured through transparency, reflexivity, and member reflection.ResultsSimilar overarching themes emerged for the quality of the training process and specific training sessions: (1) Planning and preparation (with themes such as goal setting, recovery strategies, and equipment optimization), (2) Training execution (with themes such as training load management, awareness, and solution-oriented modification of training), and (3) Coaching and training support (with themes such as trustful coach–athlete relationship, individualized interdisciplinary support, and supportive social and professional networks). These themes could influence the quality in each dimension to different extents, depending on the specific impairment and sport, and could either enhance or diminish training quality, depending on how they were addressed.ConclusionsBased on the experiences of 21 elite para-athletes, this study highlights the importance of planning and preparation, deliberate execution of training, and a competent coaching and support team to influence training quality both in the training process and specific training sessions. The extent to which the underlying factors may impact training quality, depends on impairment and sport. Athletes may improve training quality by making deliberate decisions tailored to their unique prerequisites, goals and resources. Knowledge of these factors can inform para-athletes and coaches in their efforts to enhance quality in the training process and specific training sessions.